Mapping food system vulnerabilities and multilevel governance across spatial typologies in Jambi Province - Junaidi, Junaidi; Siga, Mustaqim; Hardiani, Hardiani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2026)
Uneven production capacity, spatial disparities, distribution constraints, and governance fragmentation shape food security conditions in Jambi Province. Although aggregate indicators show improvement between 2022 and 2024, persistent territorial inequalities and structural vulnerabilities remain. This study maps food system vulnerabilities and multilevel governance dynamics across spatial typologies in Jambi Province. Using a mixed-methods design that integrates Likert-scale surveys of provincial and district/municipal officials with thematic qualitative analysis of academic perspectives, the study synthesizes institutional perceptions across the four FAO pillars—availability, access, utilization, and stability. The findings reveal scalar asymmetries in governance perceptions: provincial actors rely on aggregate indicators and formal coordination mechanisms, whereas district and municipal actors emphasize operational constraints and localized bottlenecks. Academic perspectives highlight longer-term structural pressures, including land-use conversion, climate exposure, and demographic shifts in farming communities. Through iterative thematic integration, the study constructs three spatial configurations of food system vulnerability: (1) urban and peri-urban areas dependent on external supply and sensitive to price volatility; (2) highland production centers characterized by strong output capacity but climate-related risks; and (3) rural–coastal regions constrained by infrastructural limitations and environmental exposure. The results demonstrate that food security in Jambi is territorially differentiated and mediated by multilevel governance dynamics. Mapping these configurations provides a structured basis for spatially differentiated and coordination-sensitive policy design.